Old school [compact disc, unabridged] : life in the sane lane - O'Reilly, Bill (Macmillan Audio, 2017)
You have probably heard the term Old School, but what you might not know is that there is a concentrated effort to tear that school down. It's a values thing. The anti-old school forces believe the traditional way of looking at life is oppressive. Not inclusive. The Old School way may harbor microaggressions. Therefore, Old School philosophy must be diminished. Those crusading against Old School now have a name: Snowflakes. You may have seen them on cable TV whining about social injustice and income inequality. You may have heard them cheering Bernie Sanders as he suggested the government pay for almost everything. The Snowflake movement is proud and loud, and they don't like Old School grads.